Organs and Tissue Transplantation in Human Rights and Biomedicine Perspective - Liantha Adam Nasution; Dhiauddin Tanjung (Budapest International Research and Critics University, 2022)
Organ and Tissue Transplantation Is a practice that shows successful developments in the medical world, Organ Transplantation activities are closely related to the fulfillment of human rights for living and dead donors, understanding the concept of human rights protection needs to be carried out with a biomedical approach in order to create legal protection for donors and donor recipients. This research is a normative juridical research method with library research (Library Research) in practice by examining legal concepts and legal sources that will be a reference in analyzing human rights and biomedicine. The results that can be found that the rule of law in Indonesia lacks the rights of donors and recipients of donors, reviewing the human rights of donors and accepting transplant donors in the medical aspect, so you can see the concept of Human Rights and Biomedicine.